All you need to know about NFTs / Mohd Fazil Jamaludin, Mohd Shafiz Saharan and Khairul Azfar Adzahar - Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz; Adzahar, Khairul Azfar (Universiti Teknologi MARA, Kedah, 2022)
The abbreviation NFT refers to a Non-Fungible Token, which is a type of crypto asset that utilises blockchain technology. Blockchain, on the other hand, is a digital public database of transactions, to record ownership details and offer validation of its authenticity. According to Vasan et al. (2022), a Non-Fungible Token (NFT) is a permanent and verifiable online record that links the owner of a digital artwork, frequently referred to as cryptoart. They have already mapped the Foundation platform and found over 48,000 artworks listed by over 15,000 artists through their NFTs. An NFT may be created from virtually any type of digital asset, including photographs, videos, musical compositions, texts, and even tweets. NFTs provide artists with a means to produce digital works of art and certify their work as being one-of-a-kind, everlasting, and worthy of collection. Additionally, NFTs provide collectors with the chance to present their collections on digital platforms. As a direct result, the market for digital art generated $2.5 billion in revenue during the first two quarters of 2021 (Vasan et al., 2022). Last year, one Malaysian artist’s debut NFT release grossed almost RM1.6 million, making it the most expensive batch of NFTs sold in one release during a 24-hour period by a Malaysian artist to date (Lin, 2021). Another example is the first collection of Nike's virtual sneakers. It was named Cryptokicks and consisted of 20,000 NFTs. One of the shoes in the collection was designed by the artist Takashi Murakami, and it was purchased by someone using the alias AliSajwani for the price of RM594,960 ($134,000) (Williams, 2022). Trading platforms like OpenSea, NiftyGate, SuperRare, and Foundation, amongst others, act as middlemen to facilitate the buying and selling of cryptoart (Vasan et al., 2022). Among the limited number of marketplace platforms for NFTs in Malaysia are pentas.io, NFT.my, and TRART, just to name a few. The recent suggestion made by Malaysia's Communications and Multimedia Ministry (K-KOMM) about the legalisation of activities related to mining cryptocurrencies and nonfungible tokens was met with positive feedback from individuals working in the local non-fungible token and cryptocurrency industries (Tan Su Chiat, 2022). Nevertheless, NFTs also have their fair share of controversy. Recently, The New York Times published an article titled “Thefts, Fraud and Lawsuits at the World’s Biggest NFT Marketplace”, which had a significant impact on the NFT community. The article mentions that a crypto scammer took advantage of a weakness in the OpenSea system to purchase the NFT for a price that was far lower than what it was worth. Customers also claim that OpenSea is slow to prohibit the sale of NFTs that have been taken by hackers. Hackers may make a rapid profit by flipping the stolen items, so they have an incentive to do so. The rise of stolen artwork on the platform has infuriated creators who, in the past, looked at NFTs as a potential source of sustainable income. At least four traders have filed lawsuits against the business, and last month, one of the company's former executives was arrested (Yaffe-Bellany, 2022). 21 In conclusion, there are benefits and drawbacks associated with NFTs. Since it is still relatively new, there are likely to be many critics and objections levelled against it. It is totally up to us to see it as a potential and gain something good from it.